Inside Back Cover: On Structural Features Necessary for Near‐IR‐Light Photocatalysts (Chem. Eur. J. 39/2015). Issue 39 (10th September 2015) - Wang, Gang; Huang, Baibiao; Li, Zhujie; Wang, Zeyan; Qin, Xiaoyan; Zhang, Xiaoyang; Dai, Ying; Whangbo, Myung‐Hwan
<x xml:space="preserve">Abstract</x> By studying the atomic structures, electronic structures, and NIR photocatalytic activities of Cu3(OH)4SO4, Cu4(OH)6SO4, Cu2(OH)PO4, and Cu2(OH)3Cl, B. Huang et al. have found that the presence of two different CuOm and Cu′On polyhedra linked with CuOCu′ bridges and the acceptor groups linked to the copper–oxygen polyhedra are the two conditions required for NIR‐photocatalysts. This work may lead to a search for new NIR photocatalysts in transition‐metal oxides possessing two different CuOm and Cu′On polyhedra. For more details, see their Full Paper on page 13583 ff.